2017
DOI: 10.4012/dmj.2016-258
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taper and space settings of telescopic Ce-TZP/A crowns on retentive force and settling

Abstract: The aim of this study was to investigate the effect of the taper and space setting of using Ce-TZP/A on retentive force and secondary crown settling. The taper were 2°, 4°, and 6°, and the space settings were 0 and 10 μm. The applied loads were 50 and 100 N. The taper had a significant effect on retentive force and settling at both loads (p<0.05). The space settings did not have a significant effect on retentive force or settling at either load (p<0.05). The taper of the telescopic crowns and the load affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 23 publications
2
38
0
Order By: Relevance
“…According to Körber's equation 14) , that result suggests that the taper of telescopic crowns using Ce-TZP/Al 2O3 should be smaller than that adopted when using dental alloys. In a previous study 5) , retentive force did not develop with a 6º taper but was stable at tapers of 2º and 4º. Therefore, 2º and 4º were adopted in the present study.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…According to Körber's equation 14) , that result suggests that the taper of telescopic crowns using Ce-TZP/Al 2O3 should be smaller than that adopted when using dental alloys. In a previous study 5) , retentive force did not develop with a 6º taper but was stable at tapers of 2º and 4º. Therefore, 2º and 4º were adopted in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…The retentive force of telescopic crowns is influenced by many factors, including taper and the load applied to the secondary crown [10][11][12] . In a previous study, it was reported that the initial retentive force of telescopic crowns using Ce-TZP/Al 2O3 was also influenced by both taper and load 5) . In clinical practice, telescopic crowns that have become likely to get dislodged are often encountered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations